SPACES THAT SHAPE IDENTITY AND TELL STORIES: A READING OF THE NARRATIVE OF THE COUNTRYSIDE, THE TENT AND THE DESERTIN THE POETRY OF PRINCE ABDELKADER AL JAZAIRI) - Kada AGAG & SI-MERABET Mohammed Larbi (Ziglôbitha)
Abstract: In this article, we aim to shed light on the significance of place in the poetry of Emir Abdelkaker al-Jazairi ( Emir i.e Prince) through his famous poem "The Bedouin and the Urban" (Al-Bedew and Al-Hadhar), regarding place as a narrative of civilizational identity, a story of national belonging, and a framework for social values, psychological shadows, and the civilizational dimensions it encompasses. This is in addition to the artistic formations it takes on in his work. In this context, we engage in a dialogue between the poetic work and the spatial expression, analyzing its impact on the ideas, behaviors, and lifestyles of its inhabitants.